The impact of COVID-19 on museums in the digital era: Practices and challenges in Hong Kong - Meng, Yao; Chu, Man Yin; Chiu, Dickson K.W. (Library hi tech, 2023)
PurposeDuring the coronavirus disease 2019 (COVID-19) pandemic, museums, as public gathering places for citizens, have encountered unprecedented difficulties due to limitations to operate as usual for their traditional exhibitions and curations. Thus, museums made corresponding emergency attempts to accelerate digital resource and service platform constructions. Such difficulties aroused many potential problems with the applicability of electronic resources and the mismatch between user expectations and museum services. This study investigates the challenges faced by Hong Kong museums under COVID-19, emergency responses and deliberate practices of Hong Kong museums from the perspective of both museum staff and visitors, and COVID-19's influence on the roles and functions of Hong Kong museums.Design/methodology/approachQualitative interviews with museum staff and visitors were conducted to collect opinions and experiences in the construction and maintenance of museums during the pandemic. Further thematic analyses of museum websites, evaluations, and suggestions were formulated guided by the PEST (Political, Economic, Social, Technological) and AIDA (Attention, Interest, Desire, Action) models.FindingsFindings revealed many online interactions and offline renovations, but the perceptions of visitors and staff differed considerably. While online resources and virtual museums were expanded and well received, long-term prohibitions and repressions drove physical visit desire. Participants emphasized finding a balance between user expectations and realistic practices.Originality/valueScant studies focus on the impact of COVID-19 on the cultural industry, especially in East Asia. This study also highlights new practices of digitalization and the challenges of functional transformation. The authors' findings and suggestions provide hints to optimize the curation of information resources and improve museum service quality in the new digital era. This study also serves as a reliable and meaningful record of COVID-19 impacts on Hong Kong museums.